2021
DOI: 10.1021/acs.langmuir.1c01319
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Plasma Surface Treatment on Lipid Bilayers Self-Spreading on a Polydimethylsiloxane Substrate under Different Treatment Times

Abstract: Plasma-treated poly(dimethylsiloxane) (PDMS)-supported lipid bilayers are used as functional tools for studying cell membrane properties and as platforms for biotechnology applications. Self-spreading is a versatile method for forming lipid bilayers. However, few studies have focused on the effect of plasma treatment on self-spreading lipid bilayer formation. In this paper, we performed lipid bilayer self-spreading on a PDMS surface with different treatment times. Surface characterization of PDMS treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…Hence, even though we are not directly measuring the diffusion of polymers, the FRAP results give us a good estimate of the fluidity of polymer membranes and can be used for comparative studies. The diffusion coefficient, D , we obtain for lipid bilayers on glass and PDMS substrates is in close agreement with previous measurements in the literature (Figure A). , …”
Section: Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, even though we are not directly measuring the diffusion of polymers, the FRAP results give us a good estimate of the fluidity of polymer membranes and can be used for comparative studies. The diffusion coefficient, D , we obtain for lipid bilayers on glass and PDMS substrates is in close agreement with previous measurements in the literature (Figure A). , …”
Section: Results and Discussionsupporting
confidence: 92%
“…The diffusion coefficient, D, we obtain for lipid bilayers on glass and PDMS substrates is in close agreement with previous measurements in the literature (Figure 2A). 45,46 In comparison, the diffusion coefficient of Rh-DPPE in supported PEO14-PBD22 membranes was 7−8 times smaller. Unsupported polymer membranes, as measured in PGUVs, showed a higher D but still lower than in supported lipid bilayers (Figure 2A), suggesting that interactions with the substrate account for only 2−4 times reduction in mobility.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another possibility is that PDMS material is characterized by a surface roughness of ∼3.6 nm and cavities of comparable size, leading to the formation of a PDMS–air interface inside the nanofluidic channels . We suspect that when these nanosized cavities are filled with air (e.g., water vapor), they act as air bubbles, which are known to cause damage to the cell membrane (Figure b and Supporting Information Section 1.3).…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported in several previous studies. [170][171][172] MAYER et al reported in their study that a modification of the PDMS surface using plasma exposure usually creates cracks as a side-effect, thus proposing another method toward crack-free PDMS. [171] By contrast, in this work, it was found that crack formation can be simply regulated by variation of the plasma exposure.…”
Section: Diffusive Reorganization Of Lipids In the Lipid Bilayermentioning
confidence: 99%